Maine Code of Election Ethics - Gallant, Gregory (Maine Policy Review, 2002)
In the Margaret Chase Smith Essay, Gregory Gallant discusses the voluntary Maine Code of Election Ethics, sponsored and organized by the University of Maine’s Margaret Chase Smith Policy Center and the Margaret Chase Smith Library in Skowhegan. The code is a voluntary effort designed to elevate political discourse in Maine’s federal and gubernatorial elections. Gallant reflects on the ways in which this code reinforces Margaret Chase Smith’s recognition of the critical role played by civic engagement in American society.
Keywords: Maine; election ethics